The prognostic power of major pathological response in esophageal squamous cell carcinoma patients undergoing neoadjuvant chemoimmunotherapy: a multi-center cohort study - Xie, Shuhan; Huang, Shijie; Tang, Zilu; Zhang, Hai; Xu, Jinxin; Ke, Sunkui; Xie, Jinbiao; Xu, Rongyu; Chen, Ying; Hong, Zhinuan; Kang, Mingqiang (Frontiers in Immunology, 2025)
BackgroundFor esophageal squamous cell carcinoma(ESCC), neoadjuvant chemoimmunotherapy (nICT) constitutes an innovative therapeutic strategy. However, The relationship between its short-term efficacy and long-term prognosis requires further clarification. Therefore, this study aims to evaluate the prognostic significance of major pathological response (MPR) in ESCC patients receiving nICT.MethodThis is a retrospective multi-center study enrolling 306 ESCC patients undergoing nICT. The primary endpoints were recurrence-free survival (RFS) and recurrence patterns. Propensity score matching (PSM) was applied to address heterogeneity between groups. Kaplan-Meier curves and Cox regression analysis were utilized to analyze survival difference.Results144 achieved a MPR, while 68 achieved a pathological complete response (pCR). Cox regression analysis identified MPR as an independent prognostic factor [HR = 0.48, 95%CI= (0.28 - 0.82), P = 0.007]. Survival analysis demonstrated that MPR patients experienced significantly improved RFS compared to non-MPR patients, before (P<0.001) and after PSM (P = 0.016). Importantly, the RFS of MPR patients was comparable to that of pCR patients (P = 0.319 in the unmatched cohort; P = 0.456 in the matched cohort). Furthermore, adjuvant therapy did not provide additional recurrence-free benefits for MPR patients. Compared to pCR patients, MPR patients exhibited a similar recurrence rate, with similar recurrence sites.ConclusionMPR represents a significant prognostic indicator in ESCC patients undergoing nICT, demonstrating prognostic outcomes comparable to those of pCR. These findings indicated that MPR could function as a surrogate endpoint for pCR, potentially influencing treatment strategies by refining follow-up protocol and the implementation of adjuvant therapy.